2018
DOI: 10.1111/evj.12952
|View full text |Cite
|
Sign up to set email alerts
|

Does ‘hacking’ surface type affect equine forelimb foot placement, movement symmetry or hoof impact deceleration during ridden walk and trot exercise?

Abstract: Vibration parameters generally increase as perceived surface firmness increases. Increasing speed alters vibration power but not frequency. Further investigations are required to determine the role that this may play in the development of musculoskeletal disease in horses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 32 publications
1
12
2
Order By: Relevance
“…Owing to the flexibility afforded by IMU-based gait analysis systems, a number of studies have investigated their use in clinical studies and/or for quantifying the effect of clinically relevant exercises such as flexion tests [ 13 , 14 ], before/after diagnostic analgesia [ 15 , 16 , 17 , 18 , 19 , 20 ], during lunging [ 21 , 22 , 23 , 24 , 25 , 26 ] or during movement under the rider [ 11 , 27 , 28 , 29 ]. Quantitative information is needed for creating databases, facilitating an evidence-based approach for veterinary decision making for lameness and poor performance examinations.…”
Section: Introductionmentioning
confidence: 99%
“…Owing to the flexibility afforded by IMU-based gait analysis systems, a number of studies have investigated their use in clinical studies and/or for quantifying the effect of clinically relevant exercises such as flexion tests [ 13 , 14 ], before/after diagnostic analgesia [ 15 , 16 , 17 , 18 , 19 , 20 ], during lunging [ 21 , 22 , 23 , 24 , 25 , 26 ] or during movement under the rider [ 11 , 27 , 28 , 29 ]. Quantitative information is needed for creating databases, facilitating an evidence-based approach for veterinary decision making for lameness and poor performance examinations.…”
Section: Introductionmentioning
confidence: 99%
“…Whether the horse is shod or not can also affect gait [21]. Furthermore, extensive research has found that surface type has a significant effect on the horse's kinematics [22]. Despite these reported variations, previous studies have commonly included only one breed of horse and considered only one hard, concrete-like flooring.…”
Section: Introductionmentioning
confidence: 99%
“…It is apparent that hard surfaces have different characteristics to other equestrian footings: for example, Barstow et al [9] identified higher hoof impact shock related frequencies and powers on road surfaces compared to grass and gravel. Reduced frequencies and amplitudes proximal to the fetlock joint indicate that the equine limb is efficient at damping impact shock waves [10].…”
Section: Introductionmentioning
confidence: 99%